BOOKLET DIGITAL BERBASIS AUGMENTED REALITY MATERI BILANGAN CACAH MENINGKATKAN SELF REGULATION SISWA KELAS IV SEKOLAH DASAR - Umah, Nuril Badiatul; Fatih, Mohamad; Alfi, Cindya (Universitas Negeri Medan, 2024)
The aim of this research is to develop a digital booklet based on augmented reality with whole number material to improve self-regulation of class IV students, as well as to test the effect of digital booklets based on augmented reality on self-regulation of class IV students. The method applied in this research is Research and Development (RnD) with steps in developing the ASSURE model. The experimental design used was pre-respond and post-respond with non-equivalent control group design. Based on the research results, it is known that the material validity score by material experts reached 94%, media experts reached 95%, while language experts achieved 97%, all three were categorized as very valid. Apart from that, the teacher response to the feasibility aspect reached 89% in the very feasible category. Based on student responses in the form of a questionnaire to increase self-regulation in the experimental class, the average NGain was 0.3784, while in the control class it was 0.3280. Meanwhile, to test the hypothesis using the t paired sample test, a Sig (tailed) value of 0.000 was obtained. So that 0.000<0.05, then H0 is rejected and Ha is accepted, which can be interpreted as meaning that there is an influence of augmented reality-based digital booklets on the self-regulation of class IV students at SDN 2 Tanjungsari, Blitar City.